2016
DOI: 10.1007/s11665-016-2155-8
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress in Brazing of Submicron Al2O3 to WC-Co

Abstract: This study evaluated the residual stresses induced by brazing and grinding submicron Al 2 O 3 , using different methods. Energy dispersive x-ray spectrometry analysis (EDX) of 72Ag-Cu filler and filler/WC-Co interface showed evidence of atomic diffusion and possible formation of titanium oxide layers between the joint and the bonding materials. An analytical model supported by the finite element method (FEM) based on strain determination due to the difference in variation of thermal expansion was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thus, at this stage of the manufacturing process of ceramic cutting material, the residual stresses represent 12% of the mechanical resistance of this ceramic oxide. This study does not take into account the stress of the interfaces. This work was done in a previous study which showed that an interface stress can be near the double of the surface residual stresses in a ceramic oxide and carbide cemented assembly with 191 MPa on the surface and −362 MPa at the interface. The mathematical model used in this study shows the trend distribution of the residual stresses in the ceramic layer of the brazing assembly. It is easy to use because it is only based on macroscopic properties of each layer such as: thickness, Young's modulus, thermal expansion coefficient, Poisson's ratio and thermal conditions of the brazing step.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, at this stage of the manufacturing process of ceramic cutting material, the residual stresses represent 12% of the mechanical resistance of this ceramic oxide. This study does not take into account the stress of the interfaces. This work was done in a previous study which showed that an interface stress can be near the double of the surface residual stresses in a ceramic oxide and carbide cemented assembly with 191 MPa on the surface and −362 MPa at the interface. The mathematical model used in this study shows the trend distribution of the residual stresses in the ceramic layer of the brazing assembly. It is easy to use because it is only based on macroscopic properties of each layer such as: thickness, Young's modulus, thermal expansion coefficient, Poisson's ratio and thermal conditions of the brazing step.…”
Section: Discussionmentioning
confidence: 95%
“…Residual stresses in joints have been assessed by X-Ray Diffraction (XRD) [136] and neutron diffraction [132,133,137] (it is noteworthy that stresses within filler metal layers of normal thickness have not yet been resolved due to the size of sampling volume). For joints between plates which are sufficiently thin to bend under the residual stresses, the induced curvature can be used to gauge the stress level [130], or, where the interface can be accessed, the difference in crack length generated by indentation in a stress free region and that in a region with residual stresses can be used as a measure [138]. Particular materials may allow other techniques, such as peak shifts in Raman spectroscopy where diamond [139,140] or cubic boron nitride [141] are involved in the joint.…”
Section: Advanced Brazing Systemsmentioning
confidence: 99%
“…In general, coatings prepared by a combination of vacuum cladding and flexible "coated cloth" technology have a characteristic low internal stress, controllable thickness, higher surface hardness, and better wear resistance. At the same time, flexible metal cloth can overcome the problems of complicated structures and the location of the workpiece [17][18][19].…”
Section: Introductionmentioning
confidence: 99%